2011
DOI: 10.1038/emboj.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear RNA polymerase II surveillance system targets polymerase III transcripts

Abstract: The nuclear RNA polymerase II surveillance system targets polymerase III transcriptsThe exosome and Trf4/5–Air1/2–Mtr4 polyadenylation (TRAMP) complexes together with the Nrd1–Nab3 RNA-binding heterodimer have an important role in RNA surveillance. Here, the global analysis of Nrd1, Nab3 and Trf4 binding sites identifies targets for the nuclear surveillance system, including mRNAs, ncRNAs and RNA polymerase III transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
221
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(239 citation statements)
references
References 61 publications
(125 reference statements)
16
221
2
Order By: Relevance
“…In addition to noncoding RNAs, the NNS complex has been shown to bind to a number of mRNAs (7,15,19,35,43,44). However, despite the prevalence of Nrd1-Nab3 binding to the 5= end of mRNAs, there are relatively few genes where regulation by premature termination has been confirmed (7,15,35,41,43,45).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to noncoding RNAs, the NNS complex has been shown to bind to a number of mRNAs (7,15,19,35,43,44). However, despite the prevalence of Nrd1-Nab3 binding to the 5= end of mRNAs, there are relatively few genes where regulation by premature termination has been confirmed (7,15,35,41,43,45).…”
Section: Resultsmentioning
confidence: 99%
“…The precise binding sites for Nrd1 and Nab3 can be determined from the presence of T-to-C transitions caused by the 4-thiouracil cross-link (49,50). Using these T-to-C transitions to find the binding sites, we analyzed the top 40 Nab3 binding peaks among NCR genes and found common motifs corresponding to known Nrd1 and Nab3 binding sites (Table S1) (15)(16)(17)(18)(19). Using MEME software (51), we found that the Nrd1 consensus is present in fewer genes but is more statistically significant while the Nab3 consensus is present more often but contains less information (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). In CRAC and related techniques, an increased rate of microdeletions is seen in the sequence data at the site of protein crosslinking (19,(23)(24)(25)(26). This is attributable to errors introduced by reverse transcriptase when bypassing the crosslinked site and can be used to pinpoint the precise proteinbinding site.…”
Section: High-throughput Identification Of MCMV Rnas Associated Withmentioning
confidence: 99%